Advances in the selective functionalization of B(3,6)–H of o -carboranes - Wu, Ji; Cao, Ke (Organic & biomolecular chemistry, 2025)
This review summarizes the methodologies for the selective functionalization of the B(3,6) vertices of o -carboranes, including the deboration-capitation reaction, the coupling reaction of B–X (X = I, Br) bonds, reactions of 1,3-dehydro- o -carborane and [3-N 2 - o -C 2 B 10 H 11 ][BF 4 ] as well as transition-metal-catalyzed B–H activation. These works offer a versatile toolbox for synthesizing B(3,6)-substituted o -carborane derivatives and will promote their applications in material science, pharmaceutical chemistry, and related disciplines.